Immune Correlates of COVID-19 Control - Poonia, Bhawna; Kottilil, Shyam (Frontiers in Immunology, 2020)
COVID-19 caused by SARS CoV-2 emerged in China at the end of 2019 and soon become a pandemic. Since the virus is novel, pre existing virus specific immunity does not exist in humans and this coupled with high infectiousness of the virus has resulted in massive global public health emergency. Intense efforts are on to study viral pathogenesis and immune response to help guide prophylactic and therapeutic interventions as well as epidemiological assessments like transmission modeling. To develop an effective vaccine or biologic therapeutic, it is critical to understand the immune correlates of COVID-19 control. At the same time, whether immunity in recovered individuals is effective for preventing re-infection will be important for informing interventions like social distancing. Key questions that are being investigated regarding immune response in COVID-19 which will help these efforts include, investigations of immune response that distinguishes patients with severe versus mild infection or those that recover relative to those that succumb, durability of immunity in recovered patients and relevance of developed immunity in a cured patient for protection against re-infection as well as value of convalescent plasma from recovered patients as a potential therapeutic modality. This is a broad and rapidly evolving area and multiple reports on status of innate and adaptive immunity against SARS-CoV2 are emerging on a daily basis. While most questions remain unanswered for now, the purpose of this focused review is to summarize the current understanding regarding immune correlates of COVID-19 severity and resolution in order to assist researchers in the field to pursue new directions in prevention and control.